2013
DOI: 10.1111/jpc.12191
|View full text |Cite
|
Sign up to set email alerts
|

Role of infected grandmothers in transmission of Helicobacter pylori to children in a Japanese rural town

Abstract: Aim: Although the prevalence of Helicobacter pylori (H. pylori) increases with age and the main period of acquisition is childhood, the route of transmission of H. pylori infection remains unclear. This study aims to evaluate the relationship between prevalence of children and grandparents. Methods: A total of 838 consecutive children who attended the Urita clinic and whose blood was taken for work up were enrolled in the present study. They were 449 boys and 389 girls, with a mean age of 12.4 years. H. pylori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 21 publications
(23 reference statements)
3
49
2
5
Order By: Relevance
“…There are already several reports on the prevalence of H. pylori infection in Japanese children ranging from 1.8% in Hyogo to 12% in Aomori (Supplement 1) [15][16][17][18]. The prevalence was generally lower in children than in adults [19,20], reflecting the decreasing trend of infection over the past decades.…”
Section: Discussionmentioning
confidence: 98%
“…There are already several reports on the prevalence of H. pylori infection in Japanese children ranging from 1.8% in Hyogo to 12% in Aomori (Supplement 1) [15][16][17][18]. The prevalence was generally lower in children than in adults [19,20], reflecting the decreasing trend of infection over the past decades.…”
Section: Discussionmentioning
confidence: 98%
“…Kivi et al showed that having an infected mother [OR 11.6 (95% CI: 2.0-67.9)] or at least one infected sibling [OR 8.1, (95%CI: 1.8-37.3)] was a major risk factor for H. pylori infection in Swedish children [37]. Urita et al reported a significantly higher seroprevalence of H. pylori in children who had infected siblings compared to the control group [38]. Malaty et al also provided data demonstrating an increased prevalence of infected children to infected parents [4,39].…”
Section: Discussionmentioning
confidence: 99%
“…28 Based on this study, H. pylori spread in a 3-generation households occur not only through mother to child transmission but also through the grandmother to child route. Interestingly, having an infected father or grandfather was not a significant predictor for the infection being present in children.…”
Section: Infection Transmission and Reinfectionmentioning
confidence: 99%